2022
DOI: 10.1017/dmp.2022.104
|View full text |Cite
|
Sign up to set email alerts
|

Social Determinants and Indicators of COVID-19 Among Marginalized Communities: A Scientific Review and Call to Action for Pandemic Response and Recovery

Abstract: COVID-19 has placed massive socio-psychological, health, and economic burdens including deaths on countless lives; however, it has disproportionally impacted certain populations. Co-occurring Social Determinants of Health (SDoH) disparities and other underlying determinants have exacerbated the COVID-19 pandemic. This literature review sought to (1) examine literature focused on SDoH and COVID-19 outcomes i.e., infectivity, hospitalization, and death rates among marginalized communities; and (2) identify SDoH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
2
23
0
Order By: Relevance
“…Some of them also have considered some urban factors such as urban morphology, density, housing, health facilities, urban services, and transportation on the spread of COVID-19 ( Hussein, 2022 ; Azuma et al, 2020 ; Alam and Sultana, 2021 ). Also, the effect of social variables such as ethnicity, poverty, health insurance, occupation, and socio-economic factors on the transmission of COVID-19 is reviewed in some studies ( Brakefield et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of them also have considered some urban factors such as urban morphology, density, housing, health facilities, urban services, and transportation on the spread of COVID-19 ( Hussein, 2022 ; Azuma et al, 2020 ; Alam and Sultana, 2021 ). Also, the effect of social variables such as ethnicity, poverty, health insurance, occupation, and socio-economic factors on the transmission of COVID-19 is reviewed in some studies ( Brakefield et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, these literature reviews have focused on different aspects such as urban planning factors ( Hussein, 2022 ; Rojas-Rueda and Morales-Zamora, 2021 ; Harris et al, 2022 ), urbanization ( Wu, 2021 ), density ( Zhang and Schwartz, 2020 ), transport and travel behavior features ( Shortall et al, 2021 , Shortall et al, 2022 ), environmental factors ( Azuma et al, 2020 ; Valsamatzi-Panagiotou and Penchovsky, 2022 ; Kumar et al, 2021 ; Weaver et al, 2022 ), smart city deployment ( Sharifi et al, 2021 ; Hassankhani et al, 2021 ), and social determinants of health ( Brakefield et al, 2022 ). These papers have discussed the driving factors of COVID-19 spread, how this pandemic has affected nature, settlements, and residents, and how urban planning can mitigate the negative effects of the pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Age and societal inequities (e.g., in healthcare access and socioeconomic circumstances) among populations may influence COVID-19 outcomes [17] , and it is possible that gender norms may further widen these disparities among the elderly. Initial reports indicated that 60 % of all COVID-19 patients were men, who were also at higher risk of developing systemic inflammation, multi-organ dysfunction, and cardiac injury, with viral shedding longer than women on average [18] .…”
Section: Methodsmentioning
confidence: 99%
“…As demonstrated by press coverage, efforts to “flatten the curve” were limited by public cooperation, in part due to incomplete understanding of these risks. 7–10…”
Section: Introductionmentioning
confidence: 99%